New AMS Radiocarbon Dates and a Re-evaluation of the Cultural Sequence of Tikopia Island, Southeast Solomon Islands - Kirch, Patrick V.; Swift, Jillian A. (Waka Kuaka, 2017)
The Polynesian Outlier of Tikopia, situated in the Santa Cruz Islands group (Temotu Province) of the Solomon Islands, has one of the best-defined archaeological sequences in the southwestern Pacific. Archaeological excavations in 1977-78 yielded a rich record of material culture and faunal remains, with a chronological framework provided by 20 radiocarbon dates. These dates, however, were processed on unidentified wood charcoal using the older liquid-scintillation method; the large standard errors associated with these dates rendered this chronology rather imprecise. Here we report 13 new, high-precision AMS radiocarbon dates on carbonised coconut endocarp, rat bone and pig teeth from the original excavations. The new AMS dates confirm the original sequence and, when combined with the original radiocarbon dates in a Bayesian calibration model, allow for a refinement of the cultural chronology for Tikopia. This updated model provides a more precise chronology for key events in Tikopian prehistory including first human colonisation, the arrival of Polynesian-speaking populations to the island and the formation of the sandy tombolo transforming Te Roto into a brackish-water lake.